Ablative Fractional Laser Enhances Artificial or Natural Daylight Photodynamic Therapy of Actinic Field Cancerization: A Randomized and Investigator-initiated Half-side Comparative Study - Vivian Lindholm; Mari Salmivuori; Sonja Hahtola; Kerttu Mäkelä; Sari Pitkänen; Kirsi Isoherranen (Medical Journals Sweden, 2023)
Artificial daylight photodynamic therapy is a near-painless treatment for actinic keratoses, which can be performed indoors using a controlled light dose. Daylight photodynamic therapy is approved only for treatment of grade I-II actinic keratoses. The aim of this study was to evaluate whether fractional laser pre-treatment improves the outcomes of daylight photodynamic therapy for actinic keratoses of all grades. In addition, the study compared the outcomes of artificial and natural daylight photodynamic therapy. This randomized single-blinded split-side comparative study included 60 patients with  ≥ 2 actinic keratoses of the head. Fractional laser pre-treatment was assigned randomly for actinic keratoses on 1 side of the head and, subsequently, the entire treatment area was treated with artificial or natural daylight photodynamic therapy. Fractional laser-mediated daylight photodynamic therapy achieved significantly higher complete clearance (50.0% vs 30.3%, p = 0.04), partial clearance (78.6% vs 50.0%, p < 0.01) and lesion-specific clearance (86.2% vs 70.2%, p < 0.01) than daylight photodynamic therapy alone at the 6-month follow-up. No significant differences were found in the outcomes of artificial vs natural daylight photodynamic therapy or grade I lesions vs grade II-III lesions. Thus, fractional laser pre-treatment appears to significantly increase the efficacy of artificial and natural daylight photodynamic therapy, and to be suitable for treatment of actinic keratoses of all grades.